Iron-ruthenium nanoparticles on ordered mesoporous carbon: A bimetallic nanozyme with superior peroxidase-like activity - Shamsizadeh, Mohammad Amir; Movahed, Siyavash Kazemi; Bahreini, Zahra; Chae, Keun Hwa; Khuzani, Ali Habibi (Elsevier BV, 2026)
Natural enzymes, despite their high efficiency, suffer from instability and high costs, limiting their practical use. Nanozymes which are nanomaterial-based enzyme mimics offer a robust alternative. Here, we report the design and synthesis of a bimetallic nanozyme consisting of iron and ruthenium nanoparticles that are immobilized on ordered mesoporous carbon spheres (FeRu@OMCS). This nanozyme exhibits exceptional peroxidase-like activity driven by a synergistic electronic interaction between the two metals. X-ray photoelectron spectroscopy shows charge transfer from ruthenium to iron and demonstrates this interaction. The FeRu@OMCS nanozyme has an outstandingly low Michaelis-Menten constant (Km) of 0.043 mM with the substrate tetramethylbenzidine (TMB), indicating a higher affinity for the substrate than that of its monometallic counterparts and even natural horseradish peroxidase. This work presents a rational design strategy for creating highly active, stable, and cost-effective bimetallic nanozymes for potential applications in diagnostics and catalysis.